Rohingya Crisis and the Darkside of Military in Myanmar and International Responses (Global Journal of Human-Social Science, 2021)
Rohingyas are one of the several Muslim groups in the Rakhine state of Myanmar and were regarded as the most persecuted minorities in the world. They are ethnic and religious minorities in their province and speak Rohinyalis and Bengalis rather than either Burmese or the Rakhine language and are not from a single race but from various ethnics groups, including the Arabs Moguls, and Bengalis. Sometimes they are also known as Asia's new Palestinians. The Government in Myanmar deny any recognition to them and identified them as illegal Bengali migrants from India and Bangladesh during the colonial ruled in India and Burma. The government in Myanmar also refuse to grant them citizenship status or any local documentation effectively and made them stateless. Under Myanmar's 1982 Citizenship Law, Rohingyas had been declared non-national or foreign residents. Thus, the Rohingyas are an ethnic groups who have been denying citizenship from Bangladesh and Myanmar and live their life as refugees without any security protection in both countries with uncertain future.
Keywords: rohingyalis; stateless; palestinians; migrants; tatmadaw